A review of hydrokinetic turbines and enhancement techniques for canal installations: Technology, applicability and potential. (October 2019) - Niebuhr, C.M.; van Dijk, M.; Neary, V.S.; Bhagwan, J.N.
Abstract: The hydrokinetic industry has advanced beyond its initial testing phase with full-scale projects being introduced, constructed and tested globally. However primary hurdles such as reducing the cost of these systems, optimizing individual systems and arrays and balancing energy extraction with environmental impact still requires attention prior to achieving commercial success. The present study addresses the advances and limitations of near-zero head hydrokinetic technologies and the possibility of increased potential and applicability when enhancement techniques within the design, implementation and operational phases are considered. Its goal is threefold: to review small-scale state-of-the-art near-zero hydrokinetic-current-energy-conversion-technologies, to assess barriers including gaps in knowledge, information and data as well as assess time and resource limitations of water-infrastructure owners and operators. A case study summarizes the design and implementation of the first permanent modern hydrokinetic installation in South Africa where improved outputs were achieved through optimization during each design and operation phase. An economic analysis validates a competitive levelized cost of energy and further emphasizes the broad potential that is relatively unexplored within existing water-infrastructure. Highlights: Relatively unexplored potential within water infrastructure exists for zero-head technologies. Careful selection of an optimal hydrokinetic installation site is a critical challenge. Hydrokinetic development phase enhancement measures allow an optimized system. Standards development is a critical need to advance hydrokinetic project development. Lack of awareness of hydrokinetic resource potential is a large development barrier.